Modelando Epilepsia por reprogramación y diferenciación neuronal de fibroblastos derivados de una biopsia de piel de pacientes - Casalía, Mariana Laura (2015)
We can use a technology called cell reprogramming to study a specific brain pathology using a sample of a patient?s skin. This technology allows us to convert a fibroblast into a stem cell that can be later differentiated into neurons. These neurons usually show functional characteristics of the disease studied. In our work, we aimed\nto establish a new cellular model of Epilepsy that could serve to study this disease and discover new treatments and medicines.\nEpilepsy is the third most common neurological disorder. The Benign Focal Childhood Epilepsies (BFCEs) represent the most prevalent syndromes in the pediatric population. We sought to model epilepsy using cellular reprogramming technology, from a skin biopsy of patients carrying a mutation that could be the cause\nof the epileptic phenotype. We include in the study 2 patients carrying a mutation on the FGD6 gene in homozygosis, 2 related controls carrying the mutation in heterozygosis and 1 non?related control. At least 3 clones of induced pluripotent stem cells (hIPS) from each participant was characterized as pluripotent and derived into\nneuroepithelial (NE) tissue. NE derived from epileptic patients displayed shorter axonal projections as well\nas a lower number of clusters of synapsin?1, what could be related to the delayed electrophysiological maturation that we observed in this samples.